PENINGKATAN KOMITMEN TERHADAP PROFESI MELALUI PENGUATAN PEMBERDAYAAN DAN EFIKASI DIRI GURU SMP SWASTA - Lisnawati Suparta; Widodo Sunaryo; Entis Sutisna (Universitas Pakuan, 2020)
IMPROVEMENT OF COMMITMENT TO PROFESSION THROUGH STRENGTHENING EMPOWERMENT AND SELF-EFFICATION OF PRIVATE SMP TEACHERSThis study is intended to determine the increase of organizational commitment by studying its correlation with Empowerment and Self-Efficacy of Private Junior High School Teachers located in Tapos District, Depok. The number of research samples were 106 teachers which were taken by using proportional random sampling techniques. The method used was the correlational method. Hypothesis testing was carried out using parametric statistical analysis in the form of simple and multiple linear regression analysis, simple and multiple correlation analysis and partial analysis where the significance levels α = 0.01 and α = 0.05. This study came up with three conclusions. Firstly, there was a moderate positive and significant relationship between the variables of empowerment and organizational commitment with a correlation coefficient ry1 = 0.63, a coefficient of determination Ry12 = 0.4026. Secondly, there was a high positive and significant relationship between the variable of self-efficacy and organizational commitment with a correlation coefficient ry2 = 0.81, and the coefficient of determination Ry22 = 0.6580. Thirdly, there was a high positive and significant relationship between the empowerment variable (X1) and self-efficacy (X2) together with organizational commitment with a correlation coefficient ry.12 = 0.834 and a coefficient of determination Ry.122 = 0.696. It couldn be concluded that the organizational commitment variable might be increased by strengthening the empowerment and self-efficacy variables.